2020
DOI: 10.1172/jci.insight.141443
|View full text |Cite
|
Sign up to set email alerts
|

Kir6.1- and SUR2-dependent KATP overactivity disrupts intestinal motility in murine models of Cantú syndrome

Abstract: Cantú syndrome (CS), caused by gain-of-function (GOF) mutations in pore-forming (Kir6.1, KCNJ8 ) and accessory (SUR2, ABCC9 ) ATP-sensitive potassium (K ATP ) channel subunit genes, is frequently accompanied by gastrointestinal (GI) dysmotility, and we describe 1 CS patient who required an implanted intestinal irrigation system for successful stooling. We used gene-modified mice to assess the underlying K ATP channel su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Very recently, York et al reported that mice carrying Cantú K ATP mutations also exhibit reduced intestinal contractility, potentially accounting for the gastrointestinal dysmotility frequently seen in Cantú patients. 7 This study uncovers a previously unappreciated role of the Kir6.1/SUR2B channel in the gastrointestinal tract, raising the possibility that this channel holds additional functions yet to be discovered in smooth muscles in other tissues.…”
mentioning
confidence: 66%
“…Very recently, York et al reported that mice carrying Cantú K ATP mutations also exhibit reduced intestinal contractility, potentially accounting for the gastrointestinal dysmotility frequently seen in Cantú patients. 7 This study uncovers a previously unappreciated role of the Kir6.1/SUR2B channel in the gastrointestinal tract, raising the possibility that this channel holds additional functions yet to be discovered in smooth muscles in other tissues.…”
mentioning
confidence: 66%
“…Several drugs and drug-like compounds have already been demonstrated to be pan-ABC transporter modulators interacting also with ABCA transporters. These drugs and drug-like compounds are, for example, cyclosporine A (9 targets of 4 subfamilies: ABCA1, 245 ABCB1, 20 ABCB4, 552 ABCB11, 553 ABCC1–2, 24 , 554 ABCC10, 26 and ABCG1–2 555 , 556 ), glibenclamide (8 targets of 4 subfamilies: ABCA1, 270 ABCB11, 553 ABCC1, 24 ABCC5, 557 ABCC7–9, 558 - 560 and ABCG2 554 ), imatinib (6 targets of 4 subfamilies: ABCA3, 426 ABCB1, 561 ABCB11, 553 ABCC1, 561 ABCC10, 561 and ABCG2 561 ), probenecid (8 targets of 2 subfamilies: ABCA8, 222 ABCC1–6, 24 , 26 , 562 - 564 ABCC10 565 ), verapamil (9 targets of 4 subfamilies: ABCA8, 222 ABCB1, 20 ABCB4–5, 552 , 566 ABCB11, 567 ABCC1, 24 ABCC4, 568 ABCC10, 565 and ABCG2 554 ), and verlukast (11 targets of 4 subfamilies: ABCA8, 222 ABCB4, 552 ABCB11, 553 ABCC1–5, 24 , 554 , 557 , 564 , 569 ABCC10–11, 26 , 570 ABCG2 554 ). In silico analyses with verapamil and verlukast supported the notion of addressing the multitarget binding site in ABCA7.…”
Section: Concluding Remarks: Where Do We Go From Here?mentioning
confidence: 99%
“…Therefore, in the present study we investigated lymphatic function in recently developed “Cantú” mouse models, in which CS-associated mutations in Kir6.1 (V65M) or in SUR2 (A478V or R1154Q), were introduced into the respective endogenous murine loci using CRISPR/Cas9 engineering. The systemic consequences of these mutations for cardiovascular, 11 , 12 , 32–34 skeletal muscle, 35 , 36 and gastrointestinal 37 function have been recently investigated. Mirroring what is observed in CS patients, these mice exhibit dramatically enlarged hearts with increased ejection fraction and increased contractility.…”
Section: Introductionmentioning
confidence: 99%
“…This early death is particularly prominent shortly after weaning, and potentially reflects gastro-intestinal complications, since it is partially avoided by liquid diet. 12 , 37 The most common (>30%) CS-associated variants result in mutation R1154Q (or less commonly R1154W) at a single residue in SUR2. A third mouse, in which this variant was introduced to the ABCC9 locus by CRISPR mutation, also resulted in CS-like symptoms, but these were very mild, in this case due to an additional alternate splicing consequence that results in a decrease in the number of functional channels, 34 but which appears to not occur in human tissues.…”
Section: Introductionmentioning
confidence: 99%